PEMANFAATAN MODEL PEMBELAJARAN COOPERATIVE TIPE MAKE A MATCH PADA MATA PELAJARAN FIKIH DI MTS FASTABIQUL KHAIRAT - Lestari, Eliana Ayu (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2022)
This study discusses the use of the make a match type of cooperative learning model in fiqh subjects at MTs Fastabiqul Khairat. This study aims to determine the level of conceptual understanding and creative thingking of student by applying the make a make type cooperative learning model. How is the implementation of the make a make type cooperative learning model at MTs Fastabiqul Khairat? This research use a descriptive method. With the subject 20 students taken from class VII A using the make a match learning model and VII B using conventional learning model, each subject will be interviewed to obtain information about the make a make type cooperative learning model in fiqh subjects at MTs Fastabiqul Khairat. This research was conducted form January to march. Form the result of the use of the make a match type cooperative learning model in fiqh subjects at MTs Fastabiqul Khairat, it can be seen that students will be happy to learn if a teacher is able to create a pleasant classroom atmosphere, using non-conventional learning models.